2016
DOI: 10.1007/s00709-015-0928-9
|View full text |Cite
|
Sign up to set email alerts
|

Histone acetylation and reactive oxygen species are involved in the preprophase arrest induced by sodium butyrate in maize roots

Abstract: Histone acetylation plays a critical role in controlling chromatin structure, and reactive oxygen species (ROS) are involved in cell cycle progression. To study the relationship between histone acetylation and cell cycle progression in plants, sodium butyrate (NaB), a histone deacetylase (HDAC) inhibitor that can cause a significant increase in histone acetylation in both mammal and plant genomes, was applied to treat maize seedlings. The results showed that NaB had significant inhibition effects on different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…A relationship was found between the induction of micronuclei and lipid peroxidation under several stress conditions such as Cd treatment (Souguir et al, 2011;Unyayar et al, 2006). However, a recent study made by Zhang et al (2016) indicated that ROS may be the secondary messengers in the preprophase arrest and not members of the DNA damage pathway. This hypothesis was supported by other studies where the generation of ROS did not lead to DNA damage (Green and Fluhr, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…A relationship was found between the induction of micronuclei and lipid peroxidation under several stress conditions such as Cd treatment (Souguir et al, 2011;Unyayar et al, 2006). However, a recent study made by Zhang et al (2016) indicated that ROS may be the secondary messengers in the preprophase arrest and not members of the DNA damage pathway. This hypothesis was supported by other studies where the generation of ROS did not lead to DNA damage (Green and Fluhr, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The MtTOP2 gene was up-regulated in M. truncatula radicles. Zhang et al ( 2016 ) showed that the HDAC inhibitor sodium butyrate causes the block of cell cycle at preprophase in maize root meristems, without affecting DNA integrity. Authors suggest that sodium butyrate might generate ROS acting as signaling molecules that trigger stress adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of TOP1 and TOP2 genes was also observed in maize root meristems. Zhang et al ( 2016 ) hypothesized that inhibition of topoisomerases might be a critical step in stress adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these inhibitors have been shown to partially arrest the progression of germination, thus maintaining the embryogenic potential of Pinus and spruce embryos [30] and increasing the embryogenic response in Brassica gametes [31]. Trichostatin A (TSA) and sodium butyrate (NaB) are the most widely used histone deacetylase inhibitors in plants [30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%